Islamic Education Reform in Western Contexts: Challenges and Opportunities for Teacher Professionalism - Abdusemiu Olatunji Ajani Alkilany; Ibrahim Haruna Hassan al-Wasewi; Muhammad Irfan Nazir (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze how Islamic education reform in Western developing contexts influences the redefinition of teacher professionalism within Islamic moral and epistemological frameworks. It seeks to explore the dialectic between faith-based values and secular educational structures through an interpretive conceptual review. Methodology: The research employs a qualitative literature review using the Critical Interpretive Synthesis (CIS) approach. A total of 35 academic sources from 2010–2024 were selected from Scopus, SpringerLink, and Taylor & Francis databases. The synthesis critically integrates theoretical and empirical literature on Islamic education reform, teacher professionalism, and pedagogical renewal in developing Western societies. Main Findings: The synthesis reveals that reform in Islamic education functions as an epistemological reconstruction that redefines professionalism from a moral-spiritual foundation. Teachers in Western developing contexts act as mediators between Islamic ethics and plural educational demands. Reform initiatives emphasize ta’dib (ethical discipline), ihsan (excellence), and intercultural competence as the core of teacher professionalism, transforming education into a moral and spiritual enterprise. Novelty/Originality of this study: This study contributes a conceptual framework of integrative professionalism, merging Islamic epistemology with global education theory. It offers a new understanding of how Islamic reform can serve as an ethical corrective to modern professionalism, positioning teachers as agents of spiritual renewal and social transformation in plural learning environments.